ACUTE PERITONITIS AND POSSIBLE CONNECTION WITH 5,10-METHYLENETETRAHYDROFOLATEREDUCTASE GENE POLYMORPHISMS rs1801133 AND rs1801131 - Karol, І.V.; Ziablitsev, S.V.; Bilyayeva, О.О. (World of Medicine and Biology, 2024)
The purpose of the study was to analyze the condition of patients with acute peritonitis and to establish the connection with polymorphisms of the 5,10-methylenetetrahydrofolate reductase gene rs1801133 and rs1801131. 100 patients who were operated on for peritonitis were divided into three groups by diagnosis: 1st – acute appendicitis (48 %), 2nd – acute cholecystitis (32 %) and 3rd – other diseases (22 %), including perforated stomach ulcer or duodenal (8 %), tumour perforation (3 %), abdominal trauma (3 %), pinched hernia (2 %), and intestinal obstruction (4 %). 50 people without such pathology were involved for control. The allelic polymorphism rs1801133 of the 5,10-methylenetetrahydrofolate reductase gene was connected with the development of peritonitis (except for patients with acute appendicitis): mutant allele A increased the risk of peritonitis compared to controls (OR 1.9; 95 % PI 1.06-3.49; p=0.038). The allelic polymorphism rs1801131 of the 5,10-methylenetetrahydrofolate reductase gene increased the risk of peritonitis in patients with acute appendicitis compared with all other diagnoses (OR 2.03; 95 % PI 1.07-3.84; p=0.039). The results showed that the risk of peritonitis depended on the presence of polymorphisms rs1801133 and rs1801131 of the 5,10-methylenetetrahydrofolate reductase gene.
Keywords: peritonitis; 5; 10-methylenetetrahydrofolate reductase; rs1801133; rs1801131; multiple organ failure